Psychological-Social Attitudes of Seniors Towards Stressful Situations in the Home Environment - Paľa, Gabriel; Gažiová, Mária; Gruber, Jan; Apakina, Lyudmila; Lesková, Andrea (Journal of Education Culture and Society, 2024)
Aim. The main goal of the article is to point out the attitude of seniors to stressful situations in the home environment from a psychological-social perspective. The authors identify selected categories of problem areas in the lives of seniors, which they later analyze in qualitative research. Methods. The authors used a literary-descriptive method and an open coding theory grounded in the empirical investigation of the methods. Qualitative research was carried out through interviews with seniors in which they identify burdensome problem situations and look for new solutions. start the analytical induction, the authors draw attention to new knowledge in individual problems of stress situations in seniors. Results. Seniors at home experience problematic situations associated with loneliness, loss, but also the very retirement of a partner and disrupted intergenerational relationships in the family. Home care is one of the solutions of these socio-psychological systems. Conclusion. Relationships in the family, which should be based on love, understanding, understanding and mutual help, also depend on the attitude of the senior citizen and his family towards an important situation. Relationships in the family to a large extent also affect the productivity of the senior’s family. Here, a home care service proves to be a suitable alternative and help for the family.